Compassionate Voices of Clients and Therapists in Systemic Group Psychotherapy: A Narrative Study. Issue 4 (1st October 2020) - Viou, Maria; Georgaca, Eugenie
Abstract : In this paper, we apply narrative and dialogical concepts in the study of compassion, understanding compassion as a voice emerging from psychotherapy. We analyzed two two-hour group systemic psychotherapy sessions using narrative thematic analysis. Firstly, we identified clients' inner voices in their narrative and, secondly, we tracked clients' and therapists' voices in the feedback and interventions given to group members. These voices were further categorized depending on whether they are compassionate and/or reflexive, with specific pairs of intertwined voices being identified in the group dialog. The analysis indicated that compassionate voices are part of the group process and function as a "rehearsal" before being internalized by the group members and before self-compassion is expressed. The study points to the therapists' active role in promoting the clients' compassionate reflexivity. The methodology and results of this study can be used as one method of identifying inner voices, considering the complex dialogical processes that occur in group interactions.